Non-equilibrium atmospheric pressure plasma assisted degradation of the pharmaceutical drug valsartan: influence of catalyst and degradation environment. Issue 59 (29th September 2020) - Raji, A.; Pandiyaraj, K. Navaneetha; Vasu, D.; Ramkumar, M. C.; Deshmukh, R. R.; Kandavelu, V.
Abstract : Degradation of valsartan by plasma combined with various environmental conditions. Abstract : This paper investigated the degradation of the pharmaceutical drug Valsartan (VS) using non-equilibrium atmospheric pressure plasma (NEAPP) with various operating conditions. The heterogeneous photocatalyst ZnO nanoparticles (NP's) were synthesized using a hydrothermal process. The morphology, chemical composition and structure of as-synthesized ZnO NPs were examined by Field Emission Scanning Electron Microscopy (FE-SEM), Fourier Transform Infrared Spectroscopy (FTIR) and X-ray diffraction (XRD) analysis. Then, VS degradation was examined in three subsequent treatment conditions including plasma treatment alone, the combination of plasma with as-prepared ZnO NPs and various environments (air, oxygen and hydrogen peroxide) at fixed plasma operating potential and treatment time. The degradation efficiency of plasma-treated VS by various conditions was observed using UV-visible spectroscopy. Optical Emission Spectrometry (OES) was used to characterize the distribution and emission intensity of various reactive species (OH˙, N2 -SPS and O) during the degradation processes which plays a vital role in the degradation of VS. The role of OH˙ and H2 O2 during the degradation process was further examined by chemical dosimetry and spectroscopic techniques. Furthermore, pH, conductivity and TOC of the untreated and plasma-treated VS were also investigated. The results on the degradation of VS showed that plasma treatment combined with ZnO NP's has a significant effect on degradation of molecules of VS than degradation processes carried out by other experimental conditions due to the formation of higher concentrations of various reactive oxygen and nitrogen species during the degradation processes.